EVALUATING THE IMPACT OF MAINTENANCE TO ABRASION RESISTANCE AND TEAR STRENGTH OF COATED FABRICS - Traumann, Ada; Beilmann, Merje; Tuulik, Diana (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The purpose of this paper was to evaluate the impact of maintenance to some mechanical properties of coated fabrics. Polyester is often used for outerwear because of its high durability. Coating application enhances several physical – mechanical properties of fabric. The reverse side of the test fabrics were laminated with a thin layer of the membrane to ensure complete water resistance. Since the micro-pores are sufficiently small, they will not let water through, but they let vapour through from inside to outside. It makes these kind fabrics vapour-permeable and therefore very comfortable for wearing. Although we can damage the micro-pores in the fabric very quickly whether by false maintenance mode at home for washing or drying. Test fabrics of this study were chosen from kid`s outerwear collection. Kids are good for testing of ready to wear garments but this time, the emphasis was on laboratory tests of basic fabrics. The aim of this study was to test the outer fabric under the conditions of domestic care and thereafter to carry out tests on abrasion resistance and tearing of cared fabrics.